DNA Barcoding and Ecology of Myrmecophilous Lepidoptera in Endau-Rompin, Johor - Wong, Wai Hong; Yap, Jing Wei (Enhanced Knowledge in Sciences and Technology, 2025)
The identification of myrmecophilous Lepidoptera, particularly the caterpillar and pupae found inside the ant nests, can be difficult to determine using the traditional morphological identification methods. DNA barcoding technique can help to solve these problems as it is able to identify the species of the specimen whether the specimen is incomplete, damaged, or in the immature stage. In the Endau-Rompin Forest Complex, the samples were manually collected. To ensure reliable species identification, both morphological techniques and DNA barcoding were used. DNA was extracted, and the cytochrome c oxidase subunit 1 (CO1) gene was amplified and sequenced. A total of five Lepidoptera specimens and two host ants were collected in this study. Phylogenetic analysis of the CO1 sequences successfully identified two Lepidoptera samples to the species level, while one was identified to the family level. One Lepidoptera sample failed to amplify during the PCR amplification process. This study had updated Endau-Rompin's checklist by identifying Anthene emolus, which had not before been documented in the area. Adult Spalgis epius was found living alongside with the ant host Anoplolepis gracilipes on the same plants, indicating a potential myrmecophilous association. In addition, the pupa of a species from the family Pyralidae was discovered within the ant nest of Crematogaster sp., suggesting a possible link between the host ant and the Pyralidae species.